1996
DOI: 10.1523/jneurosci.16-07-02373.1996
|View full text |Cite
|
Sign up to set email alerts
|

Chronic hyponatremia reduces survival of magnocellular vasopressin and oxytocin neurons after axonal injury

Abstract: Axonal injury to hypothalamic magnocellular vasopressin (AVP) and oxytocin (OT) neurons causes degeneration of a substantial subpopulation of these neurons. In this study, we investigated the influence of osmolality on this injury-induced cell death. Normonatremic, chronically hypernatremic, and chronically hyponatremic rats received pituitary stalk compression (SC), which causes degeneration of AVP and OT terminals in the neurohypophysis. Twenty-one days after SC, rats were perfused and hypothalami were seria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
20
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 28 publications
6
20
0
Order By: Relevance
“…The slightly greater cell death found in the VP MCNs in our experiments may be attributable to the more proximal site of the injury. The greater vulnerability of the VP MCNs versus the OT MCNs to the axotomy-induced cell death in our experiments (Table 1) is in agreement with other reports in which different modes of axonal injury were used (Herman et al, 1987;Dohanics et al, 1992Dohanics et al, , 1996Alonso et al, 1996). In addition, we observed the expected polydipsia and polyuria in the ME lesioned rats (data not shown), typical of the diabetes insipidus found after injuries to the neurohypophysial axons (O'Connor, 1952;Moll, 1962;Dellmann, 1973;Raisman, 1973;Dellmann et al, 1988).…”
Section: Effectiveness Of Me Compression To Produce Mcn Cell Deathsupporting
confidence: 92%
See 4 more Smart Citations
“…The slightly greater cell death found in the VP MCNs in our experiments may be attributable to the more proximal site of the injury. The greater vulnerability of the VP MCNs versus the OT MCNs to the axotomy-induced cell death in our experiments (Table 1) is in agreement with other reports in which different modes of axonal injury were used (Herman et al, 1987;Dohanics et al, 1992Dohanics et al, , 1996Alonso et al, 1996). In addition, we observed the expected polydipsia and polyuria in the ME lesioned rats (data not shown), typical of the diabetes insipidus found after injuries to the neurohypophysial axons (O'Connor, 1952;Moll, 1962;Dellmann, 1973;Raisman, 1973;Dellmann et al, 1988).…”
Section: Effectiveness Of Me Compression To Produce Mcn Cell Deathsupporting
confidence: 92%
“…The results showed that the compression alone produced an 83% decrease in VP MCNs and a 32% decrease in OT MCNs in the SON compared with the unlesioned control rat SONs (Table 1). The extent of this MCN cell death found in the SON after axonal compression in the ME is comparable with the 65% decrease in VP MCNs and a 31% decrease in OT MCNs in the SON found by Dohanics et al (1996) after compressing the neurohypohysial stalk. The slightly greater cell death found in the VP MCNs in our experiments may be attributable to the more proximal site of the injury.…”
Section: Effectiveness Of Me Compression To Produce Mcn Cell Deathsupporting
confidence: 78%
See 3 more Smart Citations